The Series Bridge Converter (SBC): design of a compact modular multilevel converter for grid applications - Amankwah, Emmanuel K.; Costabeber, Alessando; Watson, Alan James; Trainer, David; Jasim, Omar; Chivite-Zabalza, Javier; Clare, Jon C. (2016)
This paper presents a novel hybrid modular multilevel voltage source converter suitable for grid applications. The proposed converter retains the advantages of other modular multilevel topologies and can be made more compact making it attractive for offshore stations and other footprint critical applications like city infeeds. In this paper, the basic operating principle and design criteria for the converter implementation are presented. The submodule capacitor requirements which have significant influence on the size of a converter station are also evaluated and compared to the MMC. The performance of the converter is supported by simulation results from a representative medium voltage scaled demonstrator.